ANALISIS KESALAHAN SISWA DALAM MENYELESAIKAN SOAL MATEMATIKA PADA PEMBELAJARAN DARING - Mutiara Apriliyani Nur Hakim; Benny Hendriana (IKIP Siliwangi, 2022)
This research is motivated by the many obstacles that occur when online learning takes place so that many students experience difficulties in capturing and understanding the material which then becomes a factor in students making mistakes. This research was conducted with the aim of analyzing the errors, their causes and describing them in writing. The research was conducted at SMP Negeri 200 Jakarta in class IX-A with a total of 34 students and a sample of 5 students. Research with descriptive qualitative method. Data collection was carried out using 5 description questions and interviews. The data analysis technique in this study uses reduction, presentation and conclusion drawing, Based on the data obtained and analyzed, this study shows that 5 out of 5 students (100%) have not been able to solve the quadratic equation. It can be said that the results of student completion there are still conceptual, procedural and technical errors.